Targeting Immune Checkpoint Molecules to Eliminate Latent HIV - Boyer, Zoe; Palmer, Sarah (Frontiers in Immunology, 2018)
The advent of antiretroviral therapy (ART) has seen a dramatic decrease in the morbidity and mortality of individuals infected with human immunodeficiency virus (HIV). However, ART is not curative and HIV persists in treated individuals within a pool of infected CD4+ memory T cells. The targeting and elimination of these cells, termed the latent HIV reservoir, may be essential in establishing a cure for HIV. Current HIV reservoir research is focused on identifying cells that harbor latent, replication-competent, HIV provirus using specific cell surface markers. Recently, studies have turned to immune checkpoint (IC) molecules, such as programmed cell death protein 1 (PD-1). IC molecules are regulators of the immune system and have previously been linked to HIV infection. Furthermore, cells isolated from treated individuals co-expressing PD-1 alongside other IC molecules are enriched for HIV DNA. Administration of a IC blocking antibodies resulted in an increase of cell-associated HIV RNA within an individual, indicating the potential for this therapeutic to be utilized as a latency reversing agent. IC inhibitors could target CD4+ T cells expressing IC molecules and possibly enhance HIV transcription, allowing for the elimination of these cells by either ART or the immune system. However, treatment with IC inhibitors has been associated with toxicities such as immune-related adverse events and therefore future studies should proceed with caution.